Environmental Marine Geoscience 3. Continental Shelf Sediment Transport Studies in Canada: Theories and Recent Technology Advances - Li, Michael; Heffler, David (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2002)
Summary This article, the first of two companion papers, provides a review of recent progresses in shelf sediment transport theories and technological advances. Surficial geology and bedform mappings in the 1970s first demonstrated the existence of various bedforms over much of the Canadian shelves, and were used to deduce sediment transport processes and pathways on these shelves. Development of in situ instruments and sparse field measurements started in the early 1980s; meanwhile, primitive sediment transport models were also developed. In the last 15 years, electromagnetic current meters and optical back-scatter sensors continue to be the popular choices for velocity and suspension measurements. But various acoustic sensors provide non-intrusive, high-resolution measurements and are thus more promising. The instrumented platform RALPH developed at the Geological Survey of Canada has been continually upgraded and improved to stay at the cutting edge of shelf sediment transport technology. Sediment transport models have been significantly upgraded and calibrated based on advances incombined-flow bottom boundary layer theory and new in situ sediment transport measurements.